1985
DOI: 10.1086/268917
|View full text |Cite
|
Sign up to set email alerts
|

Face-to-Face Interviews and Mailed Questionnaires: The Net Difference in Response Rate

Abstract: THE PROSPECT of a high response rate generally has been considered a decisive argument in favor of face-to-face interviews, over mailed questionnaires. A review of methodology textbook summaries of the literature on survey response rates reveals, however, a variety of estimates of the typical response likely from these two traditional forms of data collection. Many texts caution against expecting mailed questionnaire response from a general population to exceed about 30 percent (Labovitz and Hagedorn, Abstract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0
5

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(47 citation statements)
references
References 54 publications
(25 reference statements)
1
41
0
5
Order By: Relevance
“…4 Recent random-sample anonymous mail surveys of sexual behavior in Scandinavia5,6 and Great Britain7 have had return rates of about 50% to 60%. If the sexual behavior of the group responding differs from the behavior of those not responding, nonresponse biases can affect the generalizability of the results.8 Users of such data often feel that data from surveys in which response rates are around 50% to 60% may be questionable, placing increasing authority on results from surveys with higher response rates.…”
mentioning
confidence: 99%
“…4 Recent random-sample anonymous mail surveys of sexual behavior in Scandinavia5,6 and Great Britain7 have had return rates of about 50% to 60%. If the sexual behavior of the group responding differs from the behavior of those not responding, nonresponse biases can affect the generalizability of the results.8 Users of such data often feel that data from surveys in which response rates are around 50% to 60% may be questionable, placing increasing authority on results from surveys with higher response rates.…”
mentioning
confidence: 99%
“…more recent studies (voogt and saris 2005) ask whether the combined use of different procedures might bias the results. the starting point of their study is that non-voters (abstainers) are much more inclined (more willing) to participate in face-to-face surveys than telephone surveys (Biemer 2001;day et al 1995;de leeuw and van der Zouwen 1988;Goyder 1985;Hox and de leeuw 1994). other research has shown that face-toface surveys tend to increase (overestimate) socially acceptable responses (Presser and stinson 1998;sykes and collins 1988).…”
Section: Introduction and Research Objectivesmentioning
confidence: 99%
“…Otras investigaciones tratan de estudiar cómo la falta de participación afecta a la calidad de los datos (Groves y Couper, 1998;Cohen y Carlson, 1995;Groves, Cialdini y Couper 1992;Goyder, 1985).…”
Section: Introductionunclassified